2015
DOI: 10.1037/h0101023
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in adolescence, impulsivity, and risk-taking behavior in Wistar rats.

Abstract: Adolescence is an important neurodevelopmental stage for brain sites that are related to the impulse control and reward systems. Alcohol abuse during this period may cause irreversible modifications of neural circuits that are linked to impulsivity. The present study evaluated the effects of alcohol ingestion during adolescence in Wistar rats on anxiety, risk-taking, and impulsive behavior parameters during adulthood. Male Wistar rats (n ϭ 40) were randomly assigned to 1 of 3 treatments: 0, 1, and 3 g/kg alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…McCarthy and colleagues reported that drink drivers show increased delay discounting following acute alcohol administration compared to non-drink drivers, suggesting that some individuals may be sensitive to alcohol-induced biases towards immediate rewards (McCarthy et al, 2012). Rodent studies on repeated exposure are equally inconsistent with some reports of increased temporal impulsivity in rats exposed to alcohol during adolescence (Mejia-Toiber et al, 2014), while others showing no effect of adolescence exposure on impulsivity in adulthood (Passos et al, 2015).…”
Section: Impulsivity -An Effect Of Alcoholmentioning
confidence: 99%
“…McCarthy and colleagues reported that drink drivers show increased delay discounting following acute alcohol administration compared to non-drink drivers, suggesting that some individuals may be sensitive to alcohol-induced biases towards immediate rewards (McCarthy et al, 2012). Rodent studies on repeated exposure are equally inconsistent with some reports of increased temporal impulsivity in rats exposed to alcohol during adolescence (Mejia-Toiber et al, 2014), while others showing no effect of adolescence exposure on impulsivity in adulthood (Passos et al, 2015).…”
Section: Impulsivity -An Effect Of Alcoholmentioning
confidence: 99%
“…The former includes smoking, binge drinking, drug use and unsafe sexual behaviors, and so on, whereas the latter includes bungee jumping, skiing, and diving and other risky sports. During the last decade, scholars have paid much attention to negative risk-taking behaviors, such as alcohol use ( O’Hara and Cooper, 2015 ; Passos et al., 2015 ), substance use ( Jacobus et al., 2013 ; Wood et al., 2013 ), sexual risk taking ( Downing and Bellis, 2009 ; O’Hara et al., 2012 ) and so on, because negative risk-taking behaviors not only do harm to adolescents’ physical development but also have adverse impacts on their psychosocial adaptation. For comparison, the current study also put emphasis on negative risk-taking behaviors and tried to find out those risk factors or buffers for adolescent negative risk-taking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional intelligence as a mediator can influence the degree of Internet addiction and predict such kind of activity [ 24 ]. Adolescents tend to be more prone to risky behavior and can indulge in addictive practices in order to cope with anxiety, frustration, and failure or because of the need for excitement, unrealistic optimism in relation to the feeling of invulnerability, or even the need to achieve their goals as a part of their transition into adult age [ 25 ]. The overuse of the Internet in this age group may be considered a risky behavior because it may lead to Internet addiction.…”
Section: Introductionmentioning
confidence: 99%